Switching from Beraprost to Selexipag in the Treatment of Pulmonary Arterial Hypertension: Insights from a Phase IV Study of the Japanese Registry (The EXCEL Study: EXChange from bEraprost to seLexipag Study) - Yuichi Tamura; Hiraku Kumamaru; Ichizo Tsujino; Rika Suda; Kohtaro Abe; Takumi Inami; Koshin Horimoto; Shiro Adachi; Satoshi Yasuda; Fusako Sera; Yu Taniguchi; Masataka Kuwana; et al. (MDPI AG, 2024)
Pulmonary arterial hypertension (PAH) remains a significant challenge in cardiology, necessitating advancements in treatment strategies. This study explores the safety and efficacy of transitioning patients from beraprost to selexipag, a novel selective prostacyclin receptor agonist, within a Japanese cohort. Employing a multicenter, open-label, prospective design, 25 PAH patients inadequately managed on beraprost were switched to selexipag. Key inclusion criteria included ongoing beraprost therapy for ≥3 months, a diagnosis of PAH confirmed by mean pulmonary artery pressure (mPAP) ≥ 25 mmHg, and current treatment with endothelin receptor antagonists and/or phosphodiesterase type 5 inhibitors. Outcomes assessed were changes in hemodynamic parameters (mPAP, cardiac index, pulmonary vascular resistance) and the 6 min walk distance (6-MWD) over 3-6 months. The study found no statistically significant changes in these parameters post-switch. However, a subset of patients, defined as responders, demonstrated improvements in all measured hemodynamic parameters, suggesting a potential benefit in carefully selected patients. The transition was generally well-tolerated with no serious adverse events reported. This investigation underscores the importance of personalized treatment strategies in PAH, highlighting that certain patients may benefit from switching to selexipag, particularly those previously on higher doses of beraprost. Further research is needed to elucidate the predictors of positive response to selexipag and optimize treatment regimens for this complex condition.